Operational stability of a spark ignition engine fuelled by low H2 content synthesis gas: Thermodynamic analysis of combustion and pollutants formation. (1st February 2020) - Kravos, Andraž; Seljak, Tine; Rodman Oprešnik, Samuel; Katrašnik, Tomaž
Highlights: Innovative workflow for engine optimisation using off-design fuels is developed. Positive pressure mixer is designed and optimized enabling only 16.5% power de-rating. Newly proposed optimum operating points comply with TA-Luft and EPA standard. Original engine durability is maintained and no aftertreatment systems are necessary. Abstract: The paper focuses on the implementation of a comprehensive and robust optimization procedure for a synthesis gas fired four-cylinder, spark ignited, 2.2 L industrial engine used in combined heat and power applications. Innovatively designed workflow is for the first time incorporating also a thorough operational stability analysis for evaluation of the engine operation durability while using off-design fuels. Design constraints of the engine operational space are set after in depth investigation of knock phenomena, cycle to cycle variations, emission formation phenomena and engine performance parameters. These are derived from experimental data, obtained from the engine, equipped with newly designed components. Throughout the paper, results obtained with synthesis gas are benchmarked to natural gas. With significant emphasis laid on analysis of lean operation conditions, as a measure to reduce environmental footprint of energy generation, a newly proposed optimum operation points reveal a possibility to obtain TA-Luft and EPA emission limits already with stoichiometric mixture. This allows to achieve a remarkably low power de-rating factor of only 16.5% and omission of any aftertreatment system. Therefore, findings of this study represent a significant improvement of current control strategies and enable further increase in specific power and thus economic attractiveness of distributed power generation techniques at enhanced durability while using low-carbon and renewable fuels.